An experimental and modeling study of diethyl carbonate oxidation (2015)
ABSTRACT: Diethyl carbonate (DEC) is an attractive biofuel that can be used to displace petroleum-derived diesel fuel, thereby reducing CO2 and particulate emissions from diesel engines. A better understanding of DEC combustion characteristics is needed to facilitate its use in internal combustion engines. Toward this goal, ignition delay times for DEC were measured at conditions relevant to internal combustion engines using a rapid compression machine (RCM) and a shock tube. The experimental conditions investigated covered a wide range of temperatures (660–1300 K), a pressure of 30 bar, and equivalence ratios of 0.5, 1.0 and 2.0 in air. To provide further understanding of the intermediates formed in DEC oxidation, species concentrations were measured in a jet-stirred reactor at 10 atm over a temperature range of 500–1200 K and at equivalence ratios of 0.5, 1.0 and 2.0. These experimental measurements were used to aid the development and validation of a chemical kinetic model for DEC. The experimental results for ignition in the RCM showed near negative temperature coefficient (NTC) behavior. Six-membered alkylperoxy radical () isomerizations are conventionally thought to initiate low-temperature branching reactions responsible for NTC behavior, but DEC has no such possible 6- and 7-membered ring isomerizations. However, its molecular structure allows for 5-, 8- and 9-membered ring isomerizations. To provide accurate rate constants for these ring structures, ab initio computations for isomerization reactions were performed. These new isomerization rate constants have been implemented in a chemical kinetic model for DEC oxidation. The model simulations have been compared with ignition delay times measured in the RCM near the NTC region. Results of the simulation were also compared with experimental results for ignition in the high-temperature region and for species concentrations in the jet-stirred reactor. Chemical kinetic insights into the oxidation of DEC were made using these experimental and modeling results.